Multifaceted pedagogical framework for informatics: SMP Labschool UPI perspective - Rizma Nurpriyanti (Hipkin Journal of Educational Research, 2025)
Within the Kurikulum Merdeka framework, Informatics learning occupies a strategic position as a subject that supports the development of 21st-century competencies. The purpose of this study is to examine how curriculum elements, learning models, learning media, and evaluation strategies are applied in Informatics learning at SMP Labschool UPI, particularly within the flexible Kurikulum Merdeka context. This study employed a qualitative, descriptive approach, using data collection methods such as classroom observations and in-depth interviews with Informatics teachers. The results show that teachers can independently develop lesson plans, adapt materials to students' needs, and implement various learning models, including project-based, scientific, and inquiry-based learning. The materials focused on computational thinking, Information and Communication Technology (ICT), data analysis, and the social impact of technology. The learning media included digital resources and traditional tools, and the evaluation strategy employed a backward design approach, incorporating diagnostic assessments, quizzes, reflections, and project-based assessments. This study concluded that Informatics learning under the Kurikulum Merdeka is adaptive and contextual, and can accommodate students' needs in the digital era.   Abstrak Dalam kerangka Kurikulum Merdeka, pembelajaran Informatika menempati posisi strategis sebagai mata pelajaran yang mendukung pengembangan kompetensi abad ke-21. Tujuan dari penelitian ini adalah untuk menjelaskan dan menganalisis bagaimana elemen kurikulum, model pembelajaran, media belajar, dan strategi evaluasi diterapkan dalam pembelajaran Informatika di SMP Labschool UPI, khususnya dalam konteks Kurikulum Merdeka yang fleksibel. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, melalui teknik pengumpulan data berupa observasi kelas dan wawancara mendalam dengan guru Informatika. Hasil penelitian menunjukkan bahwa guru dapat menyusun RPP secara mandiri, menyesuaikan materi dengan kebutuhan murid, dan menerapkan model pembelajaran yang bervariasi seperti pembelajaran berbasis proyek, pembelajaran ilmiah, dan berbasis inkuiri. Materi difokuskan pada berpikir komputasional, teknologi informasi dan komunikasi (TIK), analisis data, dan dampak sosial teknologi. Media pembelajaran yang digunakan mencakup sumber digital dan alat bantu tradisional, sedangkan strategi evaluasi mengikuti pendekatan backward design melalui asesmen diagnostik, kuis, refleksi, dan asesmen berbasis proyek. Studi ini menyimpulkan bahwa pembelajaran Informatika di bawah Kurikulum Merdeka bersifat adaptif, kontekstual, dan mampu mengakomodasi kebutuhan murid di era digital. Kata Kunci: evaluasi pembelajaran; Kurikulum Merdeka; pembelajaran informatika